High-tap-density iron phosphate as well as preparation method and application thereof
By controlling the synthesis process of iron phosphate, including the use of cationic surfactants and oxidants, as well as aging and calcining treatment, the problem of low iron phosphate tap density is solved, and the preparation of high-tap density iron phosphate is achieved, which has enhanced its application potential in high-performance lithium batteries.
Patent Information
- Application Number
- CN202510168019.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-05-02
AI Technical Summary
The existing industrial synthetic iron phosphate has a low tap density, which limits its application in high performance requirements.
By preparing ammonium phosphate solution, ferrous salt solution and cationic surfactant solution, reaction and oxidizing agent are performed to obtain an oxidized slurry, followed by solid-liquid separation and cleaning, phosphoric acid solution is added for aging reaction, and finally obtain high-tap density iron phosphate through calcination.
The tap density of iron phosphate is improved to 1.3~1.6g/cm3, and its application performance in lithium iron phosphate batteries is enhanced, including improving the volume energy density and specific capacity of the battery.
Smart Images

Figure CN119911887A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of ferric phosphate, and in particular to high-tap density ferric phosphate and a preparation method and application thereof. Background Art
[0002] With the rapid development of the new energy vehicle industry, the demand for lithium-ion batteries, which are its key components, has surged, which in turn has promoted the rapid expansion of related raw material industries, especially in the preparation of lithium iron phosphate batteries. Iron phosphate is a key precursor material, and its quality is directly related to the performance of the final lithium iron phosphate battery.
[0003] At present, the wet preparation process of iron phosphate is mainly divided into two technical routes: one is through Fe 3+ The second is to use Fe 2+ The iron phosphate is prepared by the combination of the iron source and the phosphorus source in the oxidation precipitation process. In the quality evaluation of iron phosphate products, the key indicators include pH value, specific surface area, iron-phosphorus ratio, tap density and trace element content. Among them, the tap density, as a key parameter to measure the bulk density of powder materials, is of great significance for the application of iron phosphate. Iron phosphate with high tap density can not only improve the stacking efficiency of materials and reduce packaging and transportation costs, but also increase its compaction density when preparing lithium iron phosphate positive electrode materials, thereby improving the volume energy density and specific capacity of the battery. However, in the existing industrial synthesis of iron phosphate technology, the process of nucleus formation and growth is often not effectively controlled, resulting in the prepared anhydrous iron phosphate primary particles are well-regularized, but the secondary agglomerated particles show irregular aggregation, and the macroscopic tap density shows a low phenomenon. The tap density of the existing industrially prepared iron phosphate is generally 0.8-1.2g / cm 3 Compared with products such as lithium cobalt oxide, lithium nickel oxide and lithium manganese oxide, this value is significantly lower, which limits the application of lithium iron phosphate batteries in situations requiring high performance. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a high tap density iron phosphate and a preparation method and application thereof, aiming to solve the technical problem of low tap density of iron phosphate.
[0005] In a first aspect, the present invention provides a method for preparing high tap density iron phosphate, comprising the following steps:
[0006] preparing ammonium phosphate solution, ferrous salt solution and cationic surfactant solution;
[0007] The cationic surfactant is placed in a reaction container, and the ammonium phosphate salt solution and the ferrous salt solution are simultaneously added into the reaction container to react, and then an oxidant is added to obtain an oxidized slurry;
[0008] The oxidized slurry is subjected to solid-liquid separation to obtain a filter cake;
[0009] The filter cake is washed and dispersed into slurry, a phosphoric acid solution is added to perform an aging reaction, and then solid-liquid separation and washing are performed to obtain ferric phosphate dihydrate;
[0010] The iron phosphate dihydrate is calcined to obtain iron phosphate with high tap density.
[0011] In the technical scheme of the embodiment of the present application, by using a cationic surfactant, the morphology and particle size of iron phosphate can be controlled; by solid-liquid separation and washing steps, impurities can be effectively removed and the purity of iron phosphate can be improved; by adding an oxidant for oxidation reaction, the oxidation process can be effectively controlled to ensure that ferrous salts are fully oxidized, thereby improving the quality of the product; by adding a high concentration of phosphoric acid solution after dispersing the filter cake into a slurry for aging reaction, the structure and performance of iron phosphate can be further optimized and its tap density can be improved; by calcining treatment, the obtained iron phosphate has good thermal stability, which is conducive to its application in high temperature environment. The preparation method of the present application is simple to operate, the conditions are controllable, it is conducive to industrial production, and has good application prospects.
[0012] In some embodiments, the preparation method of the ammonium phosphate salt solution is: add one or two of monoammonium dihydrogen phosphate, diammonium phosphate, and phosphoric acid into pure water, add ammonia water to adjust the pH value to 6-8, and obtain an ammonium phosphate salt solution; the mass concentration of phosphorus in the ammonium phosphate salt solution is 5-7%.
[0013] In this embodiment, by adjusting the mass concentration of phosphorus element, the appropriate supply of phosphorus element is ensured in the subsequent reaction process; by adjusting the pH value to 6-8, a suitable acid-base environment can be provided for the oxidation of ferrous ions and the formation of ferric phosphate, while reducing the occurrence of side reactions, such as the hydrolysis of ferrous ions, etc., thereby improving the stability and consistency of the product; by controlling the composition and concentration of the ammonium phosphate solution, the formation of ferric phosphate with a good crystal structure and high purity can be promoted, thereby improving the electrochemical properties of the final product.
[0014] In some embodiments, the cationic surfactant is a CTAB solution; and / or the oxidant is a hydrogen peroxide solution; and / or the phosphoric acid solution is a phosphoric acid solution with a mass fraction of 80-90%; and / or the ferrous salt in the ferrous salt solution is one or both of ferrous sulfate and ferrous chloride; and / or the concentration of iron in the ferrous salt solution is 0.9-1.1 mol / L.
[0015] In this embodiment, CTAB, as a cationic surfactant, helps to form stable micelles during the reaction, promotes the uniform dispersion of iron phosphate particles, reduces agglomeration, and at the same time, CTAB can also control the growth of iron phosphate particles to obtain particles of the desired particle size. Using hydrogen peroxide solution as an oxidant can effectively oxidize ferrous salts to iron salts, thereby improving reaction efficiency. During the aging process, a high concentration of phosphoric acid solution helps to adjust the morphology of iron phosphate particles, reduce the formation of irregular particles and fine particles, and make its crystal structure more complete and uniform. Through the aging reaction, the iron phosphate particles can be arranged more closely, thereby increasing their tap density. Ferrous sulfate or ferrous chloride has high activity in the reaction, which is conducive to the oxidation reaction, and its price is relatively low, which is conducive to reducing production costs. The concentration of iron in the ferrous salt solution is 0.9-1.1 mol / L, ensuring that the reaction requirements are met and a stable iron phosphate structure is formed. By controlling the concentration of ferrous salts, the occurrence of side reactions can also be reduced, and the purity and yield of the product can be improved.
[0016] In some embodiments, the mass of CTAB contained in the CTAB solution is 0.5-2% of the mass of the ferrous salt contained in the ferrous salt solution.
[0017] In this embodiment, an appropriate amount of CTAB helps to promote the formation of regular and uniform iron phosphate particles, thereby increasing the tap density of iron phosphate. CTAB can promote the reaction between ferrous salt and oxidant, improve reaction efficiency, and shorten reaction time. At the same time, the amount of CTAB is controlled within the range of 0.5-2% of the mass of ferrous salt, which can also avoid the cost increase and possible environmental pollution caused by excessive use.
[0018] In some embodiments, the molar ratio of the hydrogen peroxide contained in the hydrogen peroxide solution to the ferrous salt contained in the ferrous salt solution is (0.5-1.0):1.
[0019] In this embodiment, hydrogen peroxide is used as an oxidant, and its molar ratio with ferrous salt can ensure that the ferrous salt is fully oxidized into iron ions. Hydrogen peroxide can affect the growth process of iron phosphate particles, help to form uniform and appropriately sized particles, and improve the efficiency of converting ferrous salt to ferric phosphate, thereby increasing the yield of the final product.
[0020] In some embodiments, the molar ratio of the phosphoric acid contained in the phosphoric acid solution to the ferrous salt contained in the ferrous salt solution is (0.1-0.2):1.
[0021] In this embodiment, the addition of phosphoric acid helps to maintain an acidic environment for the formation of iron phosphate. An appropriate amount of phosphoric acid can serve as a crystal promoter to promote the formation of iron phosphate crystals, improve the crystal structure, make it more orderly and stable, and inhibit the formation of impurities to improve the purity of iron phosphate.
[0022] In some embodiments, the aging reaction temperature is 90-100° C. and the time is 1.5-2 hours.
[0023] In this embodiment, by controlling the aging reaction temperature and time, the rearrangement of the solute molecules and the growth of the crystal nuclei can be promoted to form a more perfect crystal structure.
[0024] In some embodiments, the calcination temperature is 550-650° C. and the calcination time is 2-3 hours.
[0025] In this embodiment, high temperature calcination helps to remove organic matter, impurities and residual surfactants, thereby improving the purity of iron phosphate. Appropriate calcination temperature and time help to form iron phosphate with good particle structure and high tap density.
[0026] In a second aspect, the present application provides a high tap density iron phosphate, which is prepared by the preparation method of the high tap density iron phosphate of the first aspect, wherein the tap density of the high tap density iron phosphate is 1.3 to 1.6 g / cm 3 .
[0027] In the technical solution of the embodiment of the present application, the obtained iron phosphate has a higher tap density than existing industrial products.
[0028] In a third aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material, which is prepared by a solid phase reaction of the high tap density iron phosphate described in the second aspect with a lithium source.
[0029] In this embodiment, the lithium iron phosphate positive electrode material is prepared by the above-mentioned high tap density iron phosphate, and thus also has a high compaction density and excellent electrochemical performance.
[0030] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 This is a flow chart for preparing high tap density iron phosphate in Example 1 of the present application.
[0033] Figure 2This is a diagram of the reactor apparatus used in the synthesis reaction step in Example 1 of the present application.
[0034] Figure 3 This is the XRD diffraction pattern of the high tap density iron phosphate obtained in Example 1 of the present application.
[0035] Figure 4 This is a SEM image of the high tap density iron phosphate obtained in Example 1 of the present application.
[0036] Description of reference numerals:
[0037] 1. Liquid inlet pipe for hydrogen peroxide solution; 2. Peristaltic pump; 3. Liquid inlet pipe for ammonium phosphate solution; 4. Stirring paddle; 5. Liquid inlet pipe for ferrous salt solution; 6. Reactor; 7. Water bath. DETAILED DESCRIPTION
[0038] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0040] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0041] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0042] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0043] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0044] In the existing industrial synthesis technology of iron phosphate, the process of crystal nucleus formation and growth cannot be effectively controlled, resulting in the prepared anhydrous iron phosphate primary particles being well-regular, but the secondary agglomerated particles showing irregular aggregation, and the macroscopic phenomenon of low tap density.
[0045] In order to solve the technical problem of low tap density of iron phosphate, the present application provides a high tap density iron phosphate and its preparation method and application. The iron phosphate prepared by the technical solution of the present application can increase its tap density to 1.3-1.6 g / cm while ensuring the electrical properties. 3 , and thus the compaction density of the positive electrode material is also improved.
[0046] Please refer to Figure 1 In a first aspect, the present invention provides a method for preparing high tap density iron phosphate, comprising the following steps:
[0047] S1. preparing ammonium phosphate solution, ferrous salt solution and cationic surfactant solution;
[0048] S2, placing a cationic surfactant in a reaction container, and simultaneously adding a phosphate ammonium salt solution and a ferrous salt solution into the reaction container for reaction, and then adding an oxidant to obtain an oxidized slurry;
[0049] S3, separating the oxidized slurry into solid and liquid to obtain a filter cake;
[0050] S4, washing the filter cake and dispersing it into slurry, adding phosphoric acid solution to carry out aging reaction, and then performing solid-liquid separation and washing to obtain ferric phosphate dihydrate;
[0051] S5. After calcining ferric phosphate dihydrate, high tap density ferric phosphate is obtained.
[0052] Adding ammonium phosphate solution and ferrous salt solution to the cationic surfactant at the same time can promote the coordination and precipitation reaction between iron and phosphorus to form a precursor of iron phosphate. After the ammonium phosphate solution is mixed with the ferrous sulfate solution to form a preliminary slurry, the oxidant is added to more accurately control the oxidation process, ensure that the ferrous ions are effectively oxidized to ferric ions, and avoid the side reactions caused by premature oxidation, ensuring the specificity of the reaction and the purity of the product. Through solid-liquid separation, the oxidation product generated by the reaction can be separated from the solution to obtain a filter cake. Cleaning the filter cake can remove impurities and unreacted substances and improve the purity of the product. The cleaned filter cake is dispersed into a slurry, and a high concentration of phosphoric acid solution is added for aging reaction, which is conducive to the growth of iron phosphate crystals and the optimization of the structure, and the tap density is increased. The iron phosphate is further purified by solid-liquid separation and cleaning to obtain dihydrated iron phosphate. Calcination of dihydrated iron phosphate can remove moisture from the crystal structure, promote the close arrangement of crystals, reduce porosity, and obtain anhydrous iron phosphate.
[0053] Furthermore, in some embodiments, the preparation method of the ammonium phosphate salt solution is: add one or two of monoammonium dihydrogen phosphate, diammonium phosphate, and phosphoric acid into pure water, add ammonia water to adjust the pH value to 6-8, and obtain the ammonium phosphate salt solution; the mass concentration of phosphorus element in the ammonium phosphate salt solution is 5-7%.
[0054] In the technical solution of the embodiment of the present application, the ammonium phosphate salt solution provides the necessary phosphorus source for the subsequent preparation of iron phosphate, and the mass concentration of phosphorus element is controlled at 5-7%, which can ensure that there is enough phosphorus in the solution to participate in the reaction; ammonia water is used to adjust the pH value of the ammonium phosphate salt solution, so that the degree of ionization of the ammonium phosphate salt solution is increased, and PO4 3- The increase in concentration is conducive to the precipitation of Fe elements; it can also allow the subsequent oxidation slurry to be within the precipitation pH range of FePO4 without adjusting the pH. If the pH value is too low, it may cause the dissolution of iron phosphate, and if the pH value is too high, it may cause the formation of iron hydroxide.
[0055] Furthermore, in some embodiments, the cationic surfactant is a CTAB solution; and / or the oxidant is a hydrogen peroxide solution; and / or the phosphoric acid solution is a phosphoric acid solution with a mass fraction of 80-90%; and / or the ferrous salt in the ferrous salt solution is one or both of ferrous sulfate and ferrous chloride; and / or the concentration of iron in the ferrous salt solution is 0.9-1.1 mol / L.
[0056] In the technical scheme of the embodiment of the present application, CTAB (hexadecyltrimethylammonium bromide) can form micelles in the solution, and as a template to guide the crystallization process of ferric phosphate, it helps to form uniform and regular ferric phosphate particles, thereby affecting the structure and performance of the final product. Hydrogen peroxide, as an oxidant, can ensure that ferrous ions are fully oxidized to ferric ions. During the aging process, the high concentration phosphoric acid solution provides enough phosphate ions, which helps to control the speed and direction of crystal growth and reduce the formation of defects and impurities. Phosphate ions can be used as a promoter for crystal growth, helping ferrous ions and phosphate ions to grow in a certain proportion and direction to form ferric phosphate crystals with a regular structure. At the same time, the addition of phosphoric acid solution can adjust the pH value of the system, provide a suitable acid-base environment for the synthesis of ferric phosphate, inhibit the hydrolysis and oxidation of ferric ions, thereby improving the purity and stability of ferric phosphate. Ferrous sulfate and ferrous chloride are easy to dissolve and can provide stable Fe 2+ ions, which then react with phosphate ions to form iron phosphate. The concentration of iron is preferably 0.9 to 1.1 mol / L to ensure that there is enough Fe 2+ React with phosphate ions, while avoiding too high concentration which will increase the viscosity of the solution and affect the uniformity of the reaction and the purity of the product, while too low concentration will affect the reaction efficiency.
[0057] Furthermore, in some embodiments, the mass of CTAB contained in the CTAB solution is 0.5-2% of the mass of the ferrous salt contained in the ferrous salt solution.
[0058] In the technical solution of the embodiment of the present application, CTAB can reduce the surface tension of the solution, affect the surface properties of the particles, promote the dispersion and stability of the particles, and guide the material to form a specific crystal structure. By controlling the amount of CTAB, the crystal size, morphology and structure of the final product can be affected. If the amount of CTAB is too little, it may not be able to effectively provide sufficient surfactant and template effect, resulting in particle agglomeration and irregular crystal structure; if the amount of CTAB is too much, it may cause the particles in the solution to be overly stable, making it difficult to form the desired crystal structure, producing too many by-products, and affecting the purity and performance of the material.
[0059] Furthermore, in some embodiments, the molar ratio of hydrogen peroxide contained in the hydrogen peroxide solution to the ferrous salt contained in the ferrous salt solution is (0.5-1.0):1.
[0060] In the technical solution of the embodiment of the present application, the amount of hydrogen peroxide used can ensure that the ferrous ions are fully oxidized, thereby improving the yield and quality of ferric phosphate. Excessive hydrogen peroxide may cause over-oxidation or other side reactions. Specifically, the molar ratio of hydrogen peroxide to ferrous salt can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1 or any value within the range of (0.5 to 1.0):1.
[0061] Furthermore, in some embodiments, the molar ratio of phosphoric acid contained in the phosphoric acid solution to the ferrous salt contained in the ferrous salt solution is (0.1-0.2):1.
[0062] In the technical solution of the embodiment of the present application, phosphoric acid can promote the precipitation of ferric phosphate, making the subsequent solid-liquid separation step more efficient; excessive phosphoric acid may cause excessive hydrolysis of ferrous salt, affecting the performance of the product. Specifically, the molar ratio of phosphoric acid to ferrous salt can be 0.1:1, 0.2:1 or any value within the range of (0.1 to 0.2):1.
[0063] Among them, the addition method of ammonium phosphate salt solution, ferrous sulfate solution and hydrogen peroxide solution is to add them directly below the liquid surface of CTAB solution. Since CTAB is a cationic surfactant, its solution is easy to produce foam when stirred. If it is added by dripping directly from the top, the foam floating on the upper layer will separate the added raw materials from the bottom slurry, so that the incoming raw materials cannot be quickly mixed into the bottom slurry to participate in the reaction. Specifically, controlling the introduction time of ammonium phosphate salt solution and ferrous sulfate solution to 0.5 to 2 hours can ensure that the ammonium phosphate salt solution and ferrous sulfate solution are evenly mixed in the CTAB solution, ensure that the reactants have enough time to contact and react, improve the conversion rate of the reaction and the purity of the product, avoid the reaction too fast to generate a large amount of heat, resulting in excessive local temperature, affecting the quality of the final product.
[0064] Please refer to Figure 2 , is the structural diagram of the synthesis reaction device of the oxidation slurry, and its working principle is:
[0065] The reactor 6 is placed in a water bath 7, the CTAB solution is placed in the reactor 6, three liquid inlet pipes are extended below the liquid surface, the stirring paddle 4 is continuously rotated at a certain speed, the ammonium phosphate salt solution and the ferrous salt solution enter the reactor 6 from the ammonium phosphate salt solution inlet pipe 3 and the ferrous salt solution inlet pipe 5 respectively, and the peristaltic pump 2 can control the speed of solution entry. After the ammonium phosphate salt solution and the ferrous salt solution have been completely entered, hydrogen peroxide is entered from the hydrogen peroxide solution inlet pipe 1, the reaction is completed, and an oxidized slurry is obtained.
[0066] Furthermore, in some embodiments, the aging reaction temperature is 90-100° C., and the time is 1.5-2 h.
[0067] In the technical solution of the embodiment of the present application, the temperature of the aging reaction helps to form a uniform solution, promote crystal growth, make the crystal structure more perfect, and improve the tap density of the final product. Too high a temperature may cause the crystal to grow too fast and form irregular crystals; too low a temperature may be detrimental to crystal growth. If the aging time is too short, the crystal growth is insufficient, and if the time is too long, the crystal may be too large or agglomerated.
[0068] Furthermore, in some embodiments, the calcination temperature is 550-650° C., and the calcination time is 2-3 hours.
[0069] In the technical solution of the embodiment of the present application, the appropriate temperature and time can avoid the sintering speed being too fast, thereby reducing the formation of internal stress and cracks and improving the mechanical strength of the material. Too high a temperature or too long a time may cause the iron phosphate to be over-sintered, resulting in phase change or structural damage, affecting the performance of the final product.
[0070] In a second aspect, the present invention provides a high tap density iron phosphate, which is prepared by the preparation method of the first aspect. The tap density of the high tap density iron phosphate is 1.3 to 1.6 g / cm 3 .
[0071] In the technical solution of the embodiment of the present application, the prepared iron phosphate material has an optimized crystal structure and particle morphology, which helps the particles to stack more closely, thereby increasing the tap density and making the material have better electrical conductivity and ion diffusion performance, thereby improving the compaction density of the lithium iron phosphate positive electrode material.
[0072] In a third aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material, which is prepared by a solid phase reaction of the high tap density iron phosphate of the second aspect with a lithium source.
[0073] The lithium iron phosphate positive electrode material of the present application is prepared from the above-mentioned high tap density iron phosphate, and thus has the advantage of high compaction density, thereby improving the charge and discharge efficiency and cycle stability of the battery, and improving the energy density of the battery.
[0074] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0075] 1. Preparation method
[0076] Example 1
[0077] This embodiment provides a method for preparing high tap density iron phosphate, such as Figure 1 As shown, the following steps are included:
[0078] S1. Preparation of ammonium phosphate solution: 1 mol of monoammonium dihydrogen phosphate was dissolved in 500 g of pure water to obtain a monoammonium dihydrogen phosphate solution, and aqueous ammonia was added to adjust the pH value of the solution to 7.0 to obtain an ammonium phosphate solution;
[0079] Preparation of ferrous sulfate solution: Dissolve 1.05 mol of ferrous sulfate solid in 1000 g of pure water to obtain ferrous sulfate solution.
[0080] S2. Dissolve 1.52 g of CTAB powder in 300 g of pure water to obtain a CTAB solution, and place Figure 2 In the reactor 6 shown, the ammonium phosphate solution and the ferrous sulfate solution obtained in step S1 are added below the liquid level of the CTAB solution through the ammonium phosphate solution inlet pipe 3 and the ferrous salt solution inlet pipe 5, respectively, and introduced at the same time, and the rotation speed of the peristaltic pump 2 is controlled so that the introduction speed of the ferrous sulfate solution and the ammonium phosphate solution is 1 hour. Thereafter, 91.07g of hydrogen peroxide solution (mass concentration is 28%) is introduced through the hydrogen peroxide solution inlet pipe 1. After the reaction is completed, an oxidation slurry is obtained.
[0081] S3. Use a suction filter to separate the solid and liquid of the oxidation slurry obtained in step S2, and then use pure water to wash the filter cake.
[0082] S4. Use pure water to disperse the filter cake obtained in step S3 into a slurry, add 17.29g of phosphoric acid solution (mass concentration is 85%) and age it at 98°C. After the slurry turns white, continue to keep warm for 1.5 hours, then perform solid-liquid separation, and wash the filter cake with water to obtain dihydrated iron phosphate.
[0083] S5. Calcine ferric phosphate dihydrate in a muffle furnace at a temperature of 600° C. for 2 hours to obtain ferric phosphate with a high tap density.
[0084] Example 2
[0085] This embodiment provides a method for preparing high tap density ferric phosphate. Compared with Example 1, the only difference is that the mass of CTAB powder is 0.798 g, that is, CTAB is 0.5% of the mass of ferrous salt, and the rest is basically the same as Example 1.
[0086] Example 3
[0087] This embodiment provides a method for preparing high tap density ferric phosphate. Compared with Example 1, the only difference is that the mass of CTAB powder is 3.192 g, that is, CTAB is 2% of the mass of ferrous salt, and the rest is basically the same as Example 1.
[0088] Example 4
[0089] This embodiment provides a method for preparing high tap density ferric phosphate. Compared with Example 1, the only difference is that 63.75 g of hydrogen peroxide solution is added in step S3, that is, the molar ratio of hydrogen peroxide to ferrous salt is 0.5:1, and the rest is basically the same as Example 1.
[0090] Example 5
[0091] This embodiment provides a method for preparing high tap density ferric phosphate. Compared with Example 1, the only difference is that 127.5 g of hydrogen peroxide solution is added in step S3, that is, the molar ratio of hydrogen peroxide to ferrous salt is 1:1, and the rest is basically the same as Example 1.
[0092] Example 6
[0093] This embodiment provides a method for preparing high tap density ferric phosphate. Compared with Example 1, the only difference is that 11.12 g of phosphoric acid solution is added in step S4, that is, the molar ratio of phosphoric acid to ferrous salt is 0.1:1, and the rest is basically the same as Example 1.
[0094] Example 7
[0095] This embodiment provides a method for preparing high tap density ferric phosphate. Compared with Example 1, the only difference is that 24.21 g of phosphoric acid solution is added in step S4, that is, the molar ratio of phosphoric acid to ferrous salt is 0.2:1, and the rest is basically the same as Example 1.
[0096] Comparative Example 1
[0097] Comparative Example 1 provides a method for preparing high tap density ferric phosphate. Compared with Example 1, the only difference is that no CTAB solution is added, and the rest is basically the same as Example 1.
[0098] Comparative Example 2
[0099] Comparative Example 2 provides a method for preparing high tap density ferric phosphate. Compared with Example 1, the only difference is that the mass of CTAB powder is 4.788 g, that is, CTAB is 3% of the mass of ferrous salt, and the rest is basically the same as Example 1.
[0100] Comparative Example 3
[0101] Comparative Example 3 provides a method for preparing high tap density ferric phosphate. Compared with Example 1, the only difference is that the hydrogen peroxide solution, the ammonium phosphate solution and the ferrous salt solution are added simultaneously, and the rest is basically the same as Example 1.
[0102] 2. Test Method
[0103] 1. Performance test of high tap density iron phosphate
[0104] (1) Adopting HG / T 4701-2014 standard to test Fe content, P content and Fe / P atomic ratio;
[0105] (2) Use the weight loss method to detect the moisture content in the oven;
[0106] (3) Using Malvern laser particle size analyzer to measure particle size distribution;
[0107] (4) Detecting specific surface area using adsorption method;
[0108] (5) Use a tap density meter to measure the tap density;
[0109] (6) Use ICP to detect the contents of K, Mg, Mn, and Pb;
[0110] (7) Use a pH meter to measure the pH value.
[0111] 2. Performance test of lithium iron phosphate cathode material
[0112] (1) Cyclic voltammetry was used to test the electrochemical performance;
[0113] (2) The Fe and P contents were determined by quinoline molybdate weighing method and potassium dichromate titration method, and the main element Li content was determined by flame photometry;
[0114] (3) Using Malvern laser particle size analyzer to measure particle size distribution;
[0115] (4) Detecting specific surface area using adsorption method;
[0116] (5) Use the lithium iron phosphate automatic compaction density meter to test the compaction density of lithium iron phosphate.
[0117] (6) Use ICP to detect the contents of K, Mg, Mn, and Pb.
[0118] III. Analysis of test results of various embodiments and comparative examples
[0119] Figure 3 This is the XRD diffraction pattern of the high tap density iron phosphate obtained in Example 1 of the present application. It can be seen that the X-ray diffraction analysis results show that it is anhydrous iron phosphate with JCPDF card number 29-0715.
[0120] Figure 4 This is a SEM image of the high tap density iron phosphate obtained in Example 1 of the present application. It can be seen that the iron phosphate particles are closely packed, which reduces the gaps and increases the overall density of the material. The formation process of iron phosphate precipitation includes steps such as nucleation, crystal growth and particle agglomeration. In the preparation method of the present application, due to the initial stage of Fe 3+ With P04 3- The concentration is low, the crystal nucleus grows freely, and with the addition of solution, Fe3+ With P04 3- As the concentration increases, the supersaturation increases, the nucleus formation rate is very fast, while the crystal growth rate is relatively slow or almost stops, thus obtaining a microcrystalline sol with fine particle size and good dispersion. As the reaction and nucleation proceed, the amount of solution added and the amount consumed by the reaction eventually reach a dynamic equilibrium. At this time, the Fe 3+ With P04 3- The concentration and supersaturation no longer increase, the reaction enters the crystal growth stage, the particles undergo secondary processes such as agglomeration and rupture, and finally form iron phosphate precipitation. Since the size of the precipitated particles is distributed within a certain range, there is a tendency of quasi-gradation, which makes the macroscopic tap density larger.
[0121] Specifically, the test results of the iron phosphate prepared in each embodiment and comparative example are shown in Table 1.
[0122] Table 1 Test results of iron phosphate prepared in each embodiment and comparative example
[0123]
[0124] Furthermore, the high tap density iron phosphate obtained in each embodiment and comparative example is reacted with a lithium source and a carbon source through a solid phase reaction to prepare a lithium iron phosphate positive electrode material. Specifically, the molar ratio of high tap density iron phosphate, lithium carbonate and glucose is 1:1:0.15. After the raw materials are evenly mixed, they are calcined in a nitrogen atmosphere at a temperature of 600°C. After the insulation time is 10 hours, the lithium iron phosphate positive electrode material is obtained.
[0125] Specifically, the test results of the lithium iron phosphate positive electrode material are shown in Table 2.
[0126] Table 2 Test results of lithium iron phosphate positive electrode materials
[0127]
[0128] It can be seen from Table 1 that the iron phosphate prepared in the present embodiment has a higher tap density than the existing industrial products. The tap density of the iron phosphate prepared in Comparative Example 1 is 1.19 g / cm 3 , which is lower than the tap density of the iron phosphate prepared in Example 1 (1.46 g / cm 3, indicating that CTAB helps to guide the growth of iron phosphate crystals to form particles with regular shape and size, thereby increasing the tap density of iron phosphate. In Comparative Example 2, an excess of CTAB was added, and the tap density of the prepared iron phosphate was slightly lower than that of Example 1, indicating that an appropriate amount of CTAB can more effectively guide the growth of iron phosphate crystals to form a high-density stacking structure. Excessive CTAB may lead to excessive regulation during the growth of iron phosphate crystals, affecting the growth of crystals and also increasing production costs. In Comparative Example 3, due to the simultaneous addition of hydrogen peroxide solution, ammonium phosphate solution and ferrous salt solution, the tap density of the prepared iron phosphate was reduced to 0.98g / cm 3 , indicating that this synthesis method is not conducive to the preparation of high tap density phosphoric acid. When the hydrogen peroxide solution, ammonium phosphate solution and ferrous salt solution are added simultaneously, the Fe concentration in the solution is too high. When the ammonium phosphate and hydrogen peroxide mixture is added, a portion of Fe(OH)3 will be formed due to the increase in pH value. This substance is a flocculent precipitate. During the continued addition of ammonium phosphate and hydrogen peroxide, it will be converted into iron phosphate very slowly but not completely, resulting in a decrease in the tap density of iron phosphate under this synthesis method.
[0129] Further, it can be seen from Table 2 that the lithium iron phosphate positive electrode material prepared using the high tap density iron phosphate provided in the embodiment of the present application has a higher compaction density. The tap density affects the stacking efficiency and the final compaction density of the lithium iron phosphate positive electrode material during the compaction process, thereby affecting the energy density and electrochemical performance of the battery. When high tap density iron phosphate is used to prepare lithium iron phosphate positive electrode material, its particles are more likely to remain closely arranged during the compaction process, thereby increasing the compaction density.
[0130] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing high tap density ferric phosphate, characterized in that: The following steps are involved: preparing ammonium phosphate solution, ferrous salt solution and cationic surfactant solution; The cationic surfactant solution is placed in a reaction container, and the ammonium phosphate salt solution and the ferrous salt solution are simultaneously added into the reaction container to react, and then an oxidant is added to obtain an oxidized slurry; The oxidized slurry is subjected to solid-liquid separation to obtain a filter cake; The filter cake is washed and dispersed into slurry, a phosphoric acid solution is added to perform an aging reaction, and then solid-liquid separation and washing are performed to obtain ferric phosphate dihydrate; The iron phosphate dihydrate is calcined to obtain iron phosphate with high tap density.
2. The method for preparing high tap density ferric phosphate according to claim 1, characterized in that: The preparation method of the ammonium phosphate salt solution is as follows: one or two of monoammonium dihydrogen phosphate, diammonium phosphate and phosphoric acid are added into pure water, and ammonia water is added to adjust the pH value to 6-8 to obtain the ammonium phosphate salt solution; the mass concentration of phosphorus in the ammonium phosphate salt solution is 5-7%.
3. The method for preparing high tap density ferric phosphate according to claim 1, characterized in that: The cationic surfactant solution is a CTAB solution; and / or The oxidant is a hydrogen peroxide solution; and / or The phosphoric acid solution is a phosphoric acid solution with a mass fraction of 80-90%; and / or The ferrous salt in the ferrous salt solution is one or both of ferrous sulfate and ferrous chloride; and / or, The concentration of the iron element in the ferrous salt solution is 0.9-1.1 mol / L.
4. The method for preparing high tap density ferric phosphate according to claim 3, characterized in that: The mass of CTAB contained in the CTAB solution is 0.5-2% of the mass of the ferrous salt contained in the ferrous salt solution.
5. The method for preparing high tap density ferric phosphate according to claim 3, characterized in that: The molar ratio of the hydrogen peroxide contained in the hydrogen peroxide solution to the ferrous salt contained in the ferrous salt solution is (0.5-1.0):
1.
6. The method for preparing high tap density ferric phosphate according to claim 3, characterized in that: The molar ratio of the phosphoric acid contained in the phosphoric acid solution to the ferrous salt contained in the ferrous salt solution is (0.1-0.2):
1.
7. The method for preparing high tap density ferric phosphate according to claim 1, characterized in that: The aging reaction is carried out at a temperature of 90 to 100° C. and for a time of 1.5 to 2 hours.
8. The method for preparing high tap density ferric phosphate according to claim 1, characterized in that: The calcination temperature is 550-650° C. and the calcination time is 2-3 hours.
9. A high tap density iron phosphate, characterized in that: The high tap density iron phosphate is prepared by the preparation method of high tap density iron phosphate according to any one of claims 1 to 8, and the high tap density iron phosphate has a tap density of 1.3 to 1.6 g / cm 3 .
10. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by solid phase reaction of the high tap density iron phosphate according to claim 9 and a lithium source.